Effects of prior acute exercise on circulating cytokine concentration responses to a high‐fat meal. Issue 3 (22nd August 2013) - Brandauer, Josef; Landers‐Ramos, Rian Q.; Jenkins, Nathan T.; Spangenburg, Espen E.; Hagberg, James M.; Prior, Steven J.
Abstract High‐fat meal consumption alters the circulating cytokine profile and contributes to cardiometabolic diseases. A prior bout of exercise can ameliorate the triglyceride response to a high‐fat meal, but the interactive effects of exercise and high‐fat meals on cytokines that mediate cardiometabolic risk are not fully understood. We investigated the effects of prior exercise on the responses of circulating tumor necrosis factor‐α (TNF‐α), interleukin‐6 (IL‐6), IL‐8, leptin, retinol‐binding protein 4 (RBP4), vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), placental growth factor (PlGF), and soluble fms‐like tyrosine kinase‐1 (sFlt‐1) to a high‐fat meal. Ten healthy men were studied before and 4 h after ingestion of a high‐fat meal either with or without 50 min of endurance exercise at 70% of VO2 max on the preceding day. In response to the high‐fat meal, lower leptin and higher VEGF, bFGF, IL‐6, and IL‐8 concentrations were evident (P < 0.05 for all). There was no effect of the high‐fat meal on PlGF, TNF‐α, or RBP4 concentrations. We found lower leptin concentrations with prior exercise (P < 0.05) and interactive effects of prior exercise and the high‐fat meal on sFlt‐1 (P < 0.05). The high‐fat meal increased IL‐6 by 59% without prior exercise and 218% with prior exercise (P < 0.05). In conclusion, a prior bout of endurance exercise does not affect all high‐fat meal–induced changes in circulating cytokines, but does affect fasting or postprandial concentrations of IL‐6, leptin, and sFlt‐1. These data may reflect a salutary effect of prior exercise on metabolic responses to a high‐fat meal.